Compressive Strength and Setting Times of Slump Recovery Concrete with Fly Ash - Raoupatham, Chaiyakrit; Hari Dhakal, Ram; Wanichlamlert, Chalermchai; Parnthep Julnipitawong; Tangtermsirikul, Somnuk (Science & Technology Asia, 2023)
Slump loss is a major problem of fresh concrete during construction, especially in hot climates. In this study, to retemper the concrete with loss of slump, a 2nd dose of superplasticizer is added to the concrete. With the addition of the 2nd dose of superplasticizer, the problem of slump loss can be solved; however, other concrete properties can be affected. This paper investigated the times of setting and compressive strength of the slump recovery concrete by a type F naphthalene-based superplasticizer. The concrete mixtures tested in this paper were concrete containing fly ash in the range of 0%, 30%, and 50% of the total binder. The paste volume ratios of the tested concrete were 1.2 and 1.3, whereas the water to binder ratios were varied from 0.30 to 0.58, and the initial superplasticizer dosages (SP) were applied between 0.5 to 1.6%. The setting times were tested on the mixtures at the times before and after the redosing by varying the 2nd SP dosage and time for the dosing. The results indicated that both the times of the initial and final sets were delayed by the addition of the 2nd SP dose and delayed more with the increase of the 2nd dosage. The delay was more severe in fly ash concrete when compared to cement-only concrete and the larger the fly ash replacement percentage, the longer the setting times were. The setting times were prolonged to a maximum of about 4 hrs. in the case of 50% fly ash concrete with 2nd SP dosage of 1%, whereas they were 2 hrs. in the case of 30% fly ash concrete with the same 2nd SP dosage. It was found that the incorporation of fly ash yields insignificant differences between the compressive strength of fly concrete with and without SP redosing. On the other hand, the SP redosing caused slightly lower compressive strength of cement-only concrete.